Grain growth simulation in an IF steel – Effect of grain boundary mobility. Issue 1 (April 2015) - Ayad, A; Rouag, N; Wagner, F
Abstract: In a recent paper, we have proposed a modified Potts model for the simulation of the normal grain growth stage in an IF steel. An original concept is introduced by a modular consideration of the grain size effect. It is based on experimental observations of partial textures of certain (sub) populations of grains. This allowed both better reflect the pressure at the grain boundaries and significantly speed up the calculations. This model was used to reproduce the main features of the microstructure and texture. Improvement of texture behavior, especially of the component 111<112>, which differs slightly from the experiment, requires the introduction of strong assumptions on energy and mobility of grain boundaries. The objective of this study is to verify the ability of the modified Monte Carlo model to give satisfactory results for grain growth, by considering various assumptions on energy and mobility of grain boundaries. The validity of such assumptions and their impact on the simulation results are analyzed and discussed.